ANALYSIS OF PROBLEMS IN MATHEMATICS LEARNING IN ELEMENTARY SCHOOL POST ONLINE LEARNING - Irna Dinata; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Mathematics is one of the learning content that is often considered difficult by students. After online learning, the problems in learning mathematics are increasingly diverse. This study aims to describe the problems in learning mathematics in elementary schools after online learning. This research uses qualitative research method with descriptive research type. This research was conducted at SDN Kenongo 1, Tulangan District, Sidoarjo Regency, East Java. The subject of this study was the fourth grade teacher at SDN Kenongo 1. The data collection technique used was interview. The data analysis technique used is data reduction, data presentation, and drawing conclusions. Based on the results of research that has been done, it was found several problems in learning mathematics in elementary schools after online learning, namely students experiencing difficulties in learning mathematics, students complaining when learning mathematics, students losing knowledge and skills (learning loss) due to online learning, learning models are less varied, and the achievement of student learning outcomes is low.